2006
DOI: 10.1111/j.1365-2036.2006.03127.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of fundic gland polyps during long‐term proton pump inhibitor therapy

Abstract: SUMMARY BackgroundIt is controversial whether proton pump inhibitor use leads to fundic gland polyp development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
232
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(261 citation statements)
references
References 31 publications
12
232
2
10
Order By: Relevance
“…In contrast to reports by Carmack et al (10) and Stolte et al (30), in which fundic gland polyps were reported as the most common gastric polyps, with a relative frequency of 77% and 47%, respectively, in our study, fundic gland polyps accounted for less than 6.1% of all polyps. Fundic gland polyps have almost no malignant potential when they are associated with the use of PPIs (11,31,32) or when they occur sporadically (33). Similarly, we found neither dysplasia nor malignancy in the fundic gland polyps in our study.…”
Section: Discussionmentioning
confidence: 34%
See 1 more Smart Citation
“…In contrast to reports by Carmack et al (10) and Stolte et al (30), in which fundic gland polyps were reported as the most common gastric polyps, with a relative frequency of 77% and 47%, respectively, in our study, fundic gland polyps accounted for less than 6.1% of all polyps. Fundic gland polyps have almost no malignant potential when they are associated with the use of PPIs (11,31,32) or when they occur sporadically (33). Similarly, we found neither dysplasia nor malignancy in the fundic gland polyps in our study.…”
Section: Discussionmentioning
confidence: 34%
“…In countries in which Helicobacter pylori infections are commonly seen, hyperplastic and adenomatous polyps are found to be more frequent than fundic gland polyps (8,9). In western countries, where H. pylori infections are less common and proton pump inhibitor (PPI) drug use is more common, fundic gland polyps are seen more frequently (10,11). As modern examinations of the digestive system have increased in number, gastric polyps are now detected more frequently (6).…”
Section: Introductionmentioning
confidence: 99%
“…About 70% of gastric polyps were hyperplastic, while 12% were noninvasive intramucosal neoplasias (adenomas), and 16% were fundic gland polyps. In Western countries, the most commonly encountered polyps are fundic gland polyps because H. pylori infection is less frequent and proton pump inhibitor use is common (10). The frequency and most common type of gastric polyp vary widely depending upon the population studied.…”
Section: Discussionmentioning
confidence: 99%
“…A PPI-kezelés ismerten fokozza a szérumgasztrinszin-tet, ezért elképzelhető, hogy a gasztrin-koncentráció emelkedése a gyomornyálkahártyára tropikus hatást fejt ki, és az FMP ennek a tartós hatásnak a következménye. Az irodalomban a tartós PPI-kezelés és a fundusmirigyhyperplasia oki kapcsolatával kapcsolatban pró [10,11,12] és kontra [13,14] véleményeket is olvashatunk. Saját megfi gyelésünk szerint a gyógyszer szedése és az FMP epidemiológiailag összefügghetnek.…”
Section: Megbeszélésunclassified